Instilling Pancasila Values in PPKN Through the P5 Project: Literature Review - Veronika, Nabila; Napitu, Ulung; Purba, Maria S.M; asaribu, Muldri P.J P (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research examines the implementation of the P5 in learning PPKn insecondary schools, with a focus on the literature review related to Merdeka Curriculum. The purpose of this study is to identify the impact of P5 in strengthening Pancasila values as well as the challenges faced in its implementation. The results show that P5 contributes positively in instilling Pancasila values, such as gotong royong, togetherness, and social justice. Project-based learning allows students to apply Pancasila values in daily life through social projects involving the community. However, the study also identified some challenges, such as teachers' lack of understanding of P5 and limited resources in some schools. In addition, another factor that affects the effectiveness of P5 is the limited time and facilities available. Therefore, it is recommended to improve training for teachers to implement P5 more effectively and provide adequate resources to support project-based learning. P5 has great potential in strengthening character education in Indonesia, but its implementation needs more support from various parties to achieve optimal results.